Jimmy the greatest! - Amado, Elisa; Yockteng, Rafael 1976- (Groundwood Books / House of Anansi Press, 2012)
Inspired by Muhammad Ali, Jimmy starts training to become a boxer, and while his future looks bright, he decides leaving his small town for big matches might not be the best option for him